Final Report of the Kentucky Penal Code Revision Project - Robinson, Paul H (2003)
The Kentucky Criminal Justice Council, a constitutional body in Kentucky, undertook this project to examine the problems with Kentucky criminal law and to rewrite the Kentucky criminal code. This two-volume Final Report of the Kentucky Penal Code Revision Project proposes a new criminal code, in volume 1, together with an official commentary, in volume 2, that explains each provision and how and why it differs from existing law. The introduction to the Report summarizes the reasons for and the importance of criminal code reform, and describes the techniques used in this rewrite project, including both the project’s drafting principles and the methods by which the Council organized its work on the project